Somatosensory Function in ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Somatosensory evoked potentials (SEP) and tactile function were tested in 49 ADHD children and 49 controls at the Hebrew University, Jerusalem, Israel.